WORD FORMATION OF TERMS RELATED TO COVID-19 AND THEIR EQUIVALENTS IN INDONESIAN - Sabrina, Adani Nur (Universitas Gunadarma, 2023)
Along with the spread of the Covid-19 disease, various terms that are closely related to the disease have emerged. Some are pre-existing terms, while others are specific to the disease. To find out more about terms related to Covid-19, this research was carried out with the aim of finding the word-formation of each term and how to change them into Indonesian equivalents. The method used is qualitative with descriptive analysis. The data was obtained purposively from the official web page Padanan Istilah (Pasti) provided by Indonesia's Language Development and Fostering Agency. The results of this study indicate that of the 45 terms related to Covid-19, 11 of them were formed by applying affixation, 25 by compounding, 2 by conversion, 3 by borrowing, 2 by a combination of blends and compounding, and 2 others by a combination of compounding and abbreviations. Furthermore, 15 equivalent terms were obtained using the translation technique, 14 others by the absorption technique, 1 by absorption or translation, and the remaining 15 by combining translation and absorption techniques. This research was conducted with the implication that the equivalent terms related to Covid-19 in Indonesian will be more widely used than the English version, as well as to deepen knowledge about word formation and the process of forming equivalent terms in Indonesian.